México, un refugio para el anticomunismo: el caso de Eunice Odio - Ramírez-Chávez, Lizbeth (2017)
In the twentieth century, Mexico became the homeland of several exiled or self-exiled female writers, including the Costa Rican poet Eunice Odio, whom this analysis is about. these women were forced to leave their countries due to political persecution, the intolerance or social indifference against them. Eunice’s inner and solitary search through the arduous paths of poetry leaves us several lessons: the main one is Eunice’s sound ethical position in regard to the artistic creation. However, in the context of the Cold War, she was suspected of being an agent of the Central Intelligence Agency and an accessory to the assassin of John Fitzgerald Kennedy.